Highly sensitive detection of anti-cancer drug based on bimetallic reduced graphene oxide nanocomposite. (January 2022) - Sravani, Bathinapatla; Kiranmai, S.; Rajasekhara Reddy, Gutturu; Park, Jong Pil; VeeraManohara Reddy, Y.; Madhavi, G.
Abstract: Herein, we describe a high-performance electrochemical sensor for the detection of regorafenib (REG) using bimetallic Pd–Ru nanoparticles anchored on pomegranate peel extract (PPE) derived reduced graphene oxide (Pd–Ru/rGO). PPE was employed to neutralize the extremely acidic graphene then cast-off along with the metal precursor for the duration of the chemical reduction to accomplish well dispersed Pd–Ru nanoparticles. Bimetallic Pd–Ru/rGO nanocomposites were synthesized using a facile chemical reduction method. Under optimal conditions, based on the differential pulse voltammetric studies it has been confirmed that the fabricated sensors has good electrocatalytic activity toward the detection of REG, spanning over the linear dynamic range of 0.5–300 nM. Moreover, the sensor exhibited a low limit of detection of 1.6 nM and a limit of quantification of 4.8 nM. The electrochemical sensor unveiled admirable selectivity and sensitivity, reproducibility, and repeatability. The fabricated sensor was suitable for real sample analysis (pharmaceutical tablet, human blood plasm, wastewater) with satisfactory recovery. The strategy presented herein can be employed in the development of electrochemical sensors for other target analytes. Graphical abstract: Image 1 Highlights: Bimetallic Pd–Ru/rGO nanocomposite were synthesized using a facile chemical reduction method. Pd–Ru/rGO/GC electrode investigated for the determination of regorafenib. The sensor shows excellent sensitivity, selectivity, stability, and low limit of detection. Validation of sensor through the successful determination of REG in real samples.